Identification and prevalence of intestinal parasites in schoolchildren aged 4-6 in Punturin Elementary School,Valenzuela City and Langka Day Care Center, Meycauayan, Bulacan. - Razon,June Michael V. 4 0 16; 5 (2007)
u
Thesis : (B.S. Biology) - Pamantasan ng Lungsod ng Maynila, 2007.
Keywords: 2 -- 0; 6; 20; 20; 2